2021
DOI: 10.3390/math9161896
|View full text |Cite
|
Sign up to set email alerts
|

MHD Laminar Boundary Layer Flow of a Jeffrey Fluid Past a Vertical Plate Influenced by Viscous Dissipation and a Heat Source/Sink

Abstract: This study investigates the effects of viscous dissipation and a heat source or sink on the magneto-hydrodynamic laminar boundary layer flow of a Jeffrey fluid past a vertical plate. The governing boundary layer non-linear partial differential equations are reduced to non-linear ordinary differential equations using suitable similarity transformations. The resulting system of dimensionless differential equations is then solved numerically using the bivariate spectral quasi-linearisation method. The effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This has resulted in substantial knowledge in this domain. Noteworthy contributions and studies related to squeezing flow in nanofluids can be found in recent articles [2][3][4].…”
Section: Introductionsmentioning
confidence: 99%
“…This has resulted in substantial knowledge in this domain. Noteworthy contributions and studies related to squeezing flow in nanofluids can be found in recent articles [2][3][4].…”
Section: Introductionsmentioning
confidence: 99%
“…Azaiez and Homsy [38] addressed other Jeffrey fluid models, such as the co-rotational variant. Similarly, the Jeffrey fluid model was addressed for polymeric flows [39,40], steady blood flows [41,42], steady boundary layer flows [43,44], etc.…”
Section: Introductionmentioning
confidence: 99%